Measures to Promote Creative and Safe Online Games for Children and Youth Through a Collaboration Network - Ninphet, Theeravut; Sripa, Kantita (Community and Social Development Journal, 2023)
Nowadays, children and youth have easy access to online games. Inappropriate online gaming can be harmful to young people. As a result, the purpose of this research study is to study the situation of online games and online gaming among children and youth, and to create a network of collaboration in order to develop measures to promote creative and safe online games for youth through research and development (R&D). The findings revealed that Thai children and youth play more online games, and Thailand still has legal restrictions on online game services. The measures to promote creative and safe online games for children and youth are based on the principle of "controlling and promoting", which consists of (1) controlling the manufacturing process; (2) controlling the process of providing online game services; (3) surveillance and supervision (4) promoting the production of creative and safe games; (5) promoting secure gaming online. The implementation of measures requires mechanisms at both the policy and operational levels; It should be implemented in a network affiliate manner to promote the products and services of creative and safe online games for young people.